Fatigue Analysis of Double Arc Gear Under Different Technological Condition - Jianguo Li; Ruiliang Zhang; Zhiyu Zhang (Jixie chuandong, 2019)
Taking the double arc gear as the research object， four pairs of gears with the same parameters produced under the same manufacturing conditions are tested and analyzed by different heat treatment processes， the effect of different manufacturing processes on gear performance is studied. Three loading schemes are used to study the fatigue characteristics of gear under two conditions of nitriding and unnitriding. The result show that the service life of the test gear treated with nitriding technology is about 2 times longer than that of the gear without nitriding under normal operating conditions.